Best Answer

The general idea in solving such equations it so get rid of everything, except the variable, on the left side. In this case, you have to add 16 to both sides. p - 16 = 64 p - 16 + 16 = 64 + 16 p + 0 = 80 p = 80 You can omit some of the steps when solving, I just included them for clarity: p - 16 = 64 p = 64 + 16 p = 80

The general idea in solving such equations it so get rid of everything, except the variable, on the left side. In this case, you have to add 16 to both sides. p - 16 = 64 p - 16 + 16 = 64 + 16 p + 0 = 80 p = 80 You can omit some of the steps when solving, I just included them for clarity: p - 16 = 64 p = 64 + 16 p = 80

The general idea in solving such equations it so get rid of everything, except the variable, on the left side. In this case, you have to add 16 to both sides. p - 16 = 64 p - 16 + 16 = 64 + 16 p + 0 = 80 p = 80 You can omit some of the steps when solving, I just included them for clarity: p - 16 = 64 p = 64 + 16 p = 80

The general idea in solving such equations it so get rid of everything, except the variable, on the left side. In this case, you have to add 16 to both sides. p - 16 = 64 p - 16 + 16 = 64 + 16 p + 0 = 80 p = 80 You can omit some of the steps when solving, I just included them for clarity: p - 16 = 64 p = 64 + 16 p = 80

More answers

The general idea in solving such equations it so get rid of everything, except the variable, on the left side. In this case, you have to add 16 to both sides. p - 16 = 64 p - 16 + 16 = 64 + 16 p + 0 = 80 p = 80 You can omit some of the steps when solving, I just included them for clarity: p - 16 = 64 p = 64 + 16 p = 80

Q: How do you solve this equation p - 16 equals 64?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

16

4x2 - 30 = 34 ⇒ 4x2 = 64 ⇒ x2 = 16 ⇒ x = 4 or -4

5x3 = 320 x3 = 320/5 = 64 So x = cuberoot(64) = 4

x^2 = 64 x = +,- square root of 64 = +,- 8. Thus, x = -8 or x = 8

To answer this, first convert it into an equation: (4)(x+7) = -36 Now, solve for x: (4)(x+7) = -36 4x+28 = -36 4x = )-36)-28 4x = (-36) + (-28) 4x = -64 x = (-64)/4 x = -16

Related questions

(x - 16)(x + 4) = 0 so x = -4 or 16

a-16 = a/4+2 Multiply all terms by 4: 4a-64 = a+8 4a-a = 8+64 3a = 72 a = 24

-64

8b + 16 = 64subtract 16 from both sides of the equation8b + 16 - 16 = 64 - 168b = 48divide both sides integers by 8(8/8)b = 48/8b = 6----------------check in original equation by substituting 6 in for b8(6) + 16 = 6448 + 16 = 6464 = 64-------------checks

64x = 37 Divide both sides by 64: x = 37/64 or 0.578125

-48 -16 = 20 First add -48 and -16, which = -64, which indicates that this is not an equation, because both sides are not equal. -64 â‰ 20

32 - 121 - 64 = 36x => -153 = 36x so that x = -4.25

Divide both sides by 64 to find the value of x

16

16 as a percentage of 64 = 16/64 * 100 = 25 %

64n = 25n is the percentage, so, we solve for it. In the above equation, dividing by 64 is the most suitable.n = 25/64Simplifying into a percent, we have:0.390625 = 39.0625%.

64